BAM FORM 5 – DIFFERENTIATION

Share this post on:

DIFFERENTIATION BY FIRST PRINCIPLE

Consider a curve that edu.uptymez.com 

Let A(x, f(x)) be a point on the curve let B (x + edu.uptymez.comx, f ( x + edu.uptymez.comx )) be another point on the same curve
   edu.uptymez.com

The gradient of AB

The gradient at A is given by

edu.uptymez.com

The gradient at A is given by;

edu.uptymez.com  = limit  edu.uptymez.com  

         edu.uptymez.com  edu.uptymez.com 0

edu.uptymez.com

 

Examples

Differentiate the following using first principles

y = x2+3

y = x3+2x2+1

Solution

edu.uptymez.com

Solution

edu.uptymez.com

Exercise

1) y = x3-x2

2) y = 3x2-2x

3) y = 2x2-4x+1

4) y = 12x2-6x+7

5) y = x2+2x-2

Solutions

 1) y = x3-x2

          edu.uptymez.com

TECHNIQUES OF DIFFERENTIATION

A) DERIVATIVES OF POLYNOMIAL

1) Differentiation of constant [ i.e y = c]

 edu.uptymez.com


edu.uptymez.com                                                                                                                                             

  edu.uptymez.com

edu.uptymez.com= 0

2) Differentiation of y = ax where a is a constant

                                                                                                                                                                                                                                                                      edu.uptymez.com                                                                                                                                                                                                                                                                                               

The gradient at B can be found by using the following

y = ax ………..(i)

Taking a point further

y + edu.uptymez.comy = a(x + edu.uptymez.comx)

= ax + aedu.uptymez.comx ……..(ii)

Subtracting y from (iii)

y + edu.uptymez.comy –y = ax + aedu.uptymez.comx – ax
edu.uptymez.com

edu.uptymez.com  =  edu.uptymez.com

edu.uptymez.com  = a

3) Differentiation of y = x2
edu.uptymez.com                                                                                                                                                                                                                               

At point B

y + δy

y = [x+ edu.uptymez.comx] 2

= x2 + 2x edu.uptymez.comx+ edu.uptymez.comx2  …………… (i)

Subtract y from (i)

y2+ 2xedu.uptymez.comx + edu.uptymez.comx2 – x2= y + edu.uptymez.comy – y

edu.uptymez.comy = 2xedu.uptymez.comx+ edu.uptymez.comx2…….

Dividing ….ii,  by edu.uptymez.comx …..

= edu.uptymez.com

As edu.uptymez.comx   edu.uptymez.com    0, edu.uptymez.comedu.uptymez.com  0, edu.uptymez.comy / edu.uptymez.comx = dy /dx

Equation becomes

edu.uptymez.com
Note

By proceeding with the same trend we shall get

When y = x4,edu.uptymez.com = 4x3

When y = x5, edu.uptymez.com= 5x4

When y = x6, edu.uptymez.com= 6x5

Generally

If y = xn , then

 edu.uptymez.com     = nx n-1

Example

Differentiate the following with respect to x.

edu.uptymez.com  

y = 6x7+5x4

y =-x10+9x2

Solution

       edu.uptymez.com
    

 Since differentiation of constant = 0

edu.uptymez.com

edu.uptymez.com= 3+0

edu.uptymez.com   = 3

y = 6x7+5x4-x2

edu.uptymez.com    = 42x6+20x3-2x

y =-x10+9x2

= edu.uptymez.com 

edu.uptymez.com  edu.uptymez.com =  -10x9+18x

Exercise

Differentiate the following with respect to x.

i.)     y =5x2+2

ii.)    y =8x3-15x2+6x+2

iii.)  y =x5-4x3

iv.) y = 6x2-x3+5x4

v.)  y = 3x+10x2-4x7

Solution

          y = 5x2 + 2
edu.uptymez.com  = 2[5] x[2-1] +2[0]                                                                                                        


= 10x+0

      = 10x

  = 10x

2.)   y = 8x3-15x2+6x+2

            edu.uptymez.com
= 24x2– 30x + 6

3.)   y = x5-4x3

       edu.uptymez.com = 5x4-12x2

4.)   y=6x2-x3+5x4

        edu.uptymez.com=12x-3x2+20x3

DERIVATIVE BY USING CHAIN RULE

Is used to find derivative of function

Example:

Differentiate y = [3x+5]4

Solution

Let U = 3x+5

edu.uptymez.com 

y =U4

edu.uptymez.com

edu.uptymez.com
 

4u 3 x3

= 12u3

edu.uptymez.com  = 12 [3x+5]3

Note: This process is called chain rule

2) Find the  edu.uptymez.com  if y = edu.uptymez.com

Solution

Let u = x+1

edu.uptymez.com 

y = edu.uptymez.com

y = u ½

y = ½ u– ½

edu.uptymez.com= edu.uptymez.com  x  edu.uptymez.com

= ½ u– ½ x 1

= ½ [x+1]– ½ 

Share this post on: